DEVELOPMENT OF PHYSICS-THEMED QUESTIONS IN ORDER TO IMPROVE STUDENTS' NATURAL SCIENTIFIC LITERACY - Shahnoza Anvarova Asqarjon kizi (Scholar Express Journal, 2022)
This article is devoted to the issues of increasing natural scientific literacy of the PISA international program for improving the quality of education. Samples of physics-themed questions based on PISA tasks are presented.
Keywords: TIMSS; PIRLS; PISA; Natural-scientific literacy